2019
DOI: 10.1001/jamaoncol.2018.3773
|View full text |Cite
|
Sign up to set email alerts
|

Alisertib in Combination With Weekly Paclitaxel in Patients With Advanced Breast Cancer or Recurrent Ovarian Cancer

Abstract: IMPORTANCE There is an unmet medical need for the treatment of recurrent ovarian cancer, and new approaches are needed to improve progression-free survival (PFS) and overall survival. OBJECTIVE This phase 1/2 study evaluated the activity of alisertib in combination with weekly paclitaxel in patients with breast (phase 1) and ovarian cancer (phase 1 and phase 2). DESIGN, SETTING, AND PARTICIPANTS An open-label phase 1 and randomized phase 2 clinical trial conducted from April 16, 2010, for phase 1 and March 28,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 37 publications
5
47
0
Order By: Relevance
“…Notably, neutropenia is one of the most common toxicities in clinical trials of alisertib in solid tumors (5,7,8,44). In line with these reports, we demonstrated myeloid cells are readily eliminated by alisertib in mouse mammary tumor.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Notably, neutropenia is one of the most common toxicities in clinical trials of alisertib in solid tumors (5,7,8,44). In line with these reports, we demonstrated myeloid cells are readily eliminated by alisertib in mouse mammary tumor.…”
Section: Discussionsupporting
confidence: 88%
“…The Aurora A kinase inhibitor alisertib has exhibited significant anticancer effects in preclinical studies and phase I and phase II clinical trials in multiple tumor types including refractory breast cancer (5)(6)(7)(8)44). However, it is unclear whether and how this compound directly modulates the immune microenvironment, which has been widely proved to play an important role not only in tumor progression but also in tumor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The RT-qPCR results of our seven cases of cortisol-producing ACC and the results of ACC-TCGA dataset analysis showed that mRNA of AURKA is also highly expressed in adult ACC cases with TP53 somatic variants and with atypical mitotic figures. Alisertib, an AURKA inhibitor, is currently undergoing clinical trials for various cancers [55,56,57], and it may be useful for the treatment of ACC in the future. In aggressive cases with TP53 variants, it may be more effective to administer an AURKA inhibitor in combination with conventional mitotane and combined etoposide, doxorubicin, and cisplatin therapy as adjuvant therapy.…”
Section: Plos Onementioning
confidence: 99%
“…[18][19][20][21][22][23] Single-agent activity was demonstrated in a phase II study of patients with relapsed or refractory solid tumors, including SCLC (n ¼ 48); 23 in patients with SCLC, the objective response rate (ORR) was 21% and the median progression-free survival (PFS) was 2.1 months. 23 On the basis of preclinical evidence of synergy, alisertib plus paclitaxel (henceforth referred to as alisertib/paclitaxel) was evaluated in patients with breast and ovarian cancer 19 and showed promise over paclitaxel alone, with PFS and ORR trending in favor of the combination. 19 Preclinical data have also shown alisertib/paclitaxel synergy in SCLC; increased antitumor activity with the combination versus with the single agents was demonstrated in xenograft tumor models derived from human SCLC cell lines and human SCLC primary tumors (Takeda, data on file).…”
Section: Introductionmentioning
confidence: 99%
“…23 On the basis of preclinical evidence of synergy, alisertib plus paclitaxel (henceforth referred to as alisertib/paclitaxel) was evaluated in patients with breast and ovarian cancer 19 and showed promise over paclitaxel alone, with PFS and ORR trending in favor of the combination. 19 Preclinical data have also shown alisertib/paclitaxel synergy in SCLC; increased antitumor activity with the combination versus with the single agents was demonstrated in xenograft tumor models derived from human SCLC cell lines and human SCLC primary tumors (Takeda, data on file). The preclinical and clinical data thus provided justification for this phase II study of alisertib/paclitaxel as second-line therapy for relapsed or refractory SCLC.…”
Section: Introductionmentioning
confidence: 99%